2010
DOI: 10.1111/j.1365-2982.2010.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced myoelectric activity in the sphincter of Oddi in a new model of chronic cholangitis in rabbits: an in vivo and in vitro study

Abstract: Myoelectric activity of SO and its response to agonists are decreased in rabbits with chronic cholangitis both in vivo and in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Studies have shown that the reactivity to agonists CCK-8 of rabbits with chronic cholecystitis significantly decreased, and myoelectric activity of SO and its response to agonists CCK-8 and KCI are decreased in rabbits with chronic cholangitis both in vivo and in-vitro 9 . Both clinical and experimental types of research have confirmed that acupuncture at GB34, LR14, and auricular concha has a good curative effect on corresponding biliary diseases 10 – 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the reactivity to agonists CCK-8 of rabbits with chronic cholecystitis significantly decreased, and myoelectric activity of SO and its response to agonists CCK-8 and KCI are decreased in rabbits with chronic cholangitis both in vivo and in-vitro 9 . Both clinical and experimental types of research have confirmed that acupuncture at GB34, LR14, and auricular concha has a good curative effect on corresponding biliary diseases 10 – 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In the guinea pig lithogenic model, EMG was used to detect the myoelectric difference in the Oddi sphincter at different stages under a high cholesterol diet, indicating that Oddi sphincter dysfunction caused by a high cholesterol diet may be one of the pathogenic mechanisms of cholesterol gallstones[ 86 ]. Liu et al [ 87 ] also found Oddi sphincter dysfunction in rabbits with chronic cholangitis and proved that the intracellular calcium mobilization pathway was involved in the relaxation of the sphincter under pathological conditions.…”
Section: Electrophysiological Research On the Gallbladder And Biliary...mentioning
confidence: 99%